A PRELIMINARY ACCOUNT OF THE FRAMEWORK GRAIN COMPOSITION AND PROVENANCE OF THE LOWER TERTIARY SANDSTONE OUTCROPPED IN THE OMBILIN BASIN, CENTRAL SUMATRA - -, Billy G. Adhiperdana (Bulletin of Scientific Contribution, 2010)
The outcrop findings of the inverted Basin fill in the Ombilin Basin Central Sumatra, provides a new opportunity for research into provenance and sediment dispersal system. Sandstone samples were taken for petrographic examination from the Eocene Brani Formation, the Oligocene Sawahlunto Formation and the Miocene Ombilin Formation.Major diagenetic features such as compaction, cementation, replacement and grain deformation are commonly present in all samples, but however they exhibit a different intensity level and variation in detail to each formation.Metamorphic rock fragment, marble rock fragment and plagioclase grain are the distinctive grain types (petrographic classes) of the Brani Formation sandstone. Petrographic classes that characterize the overall populated sandstone of the Sawahlunto Formation consist of undulosed monocrystalline quartz and lithic chert. Petrographic classes that characterize the overall populated sandstone of the Ombilin Formation comprises sedimentary rock fragment (authigenic grain and intrabasinal clast) and lithic volcanic. In terms of parental rock assemblage, it is identified that the provenance (parental rock) of the sand grain in the three formations are possibly sourced from five rock assemblages: A). Pre Tertiary Extrabasinal sediment and volcanic; B). Pre Tertiary Extrabasinal Metamorphic; C). Extrabasinal contemporaneous volcanism; D). Intrabasinal contemporaneous sediment; E). Pre Tertiary Extrabasinal granitoid pluton.